Creating an enabling environment and accelerating SDGs through increased public funding of innovative agricultural research and development - Menza, Gianpiero; Steele, Megan; Seke, Lukovi; Akinbo, Olalekan (2023)
G20 policymakers should strengthen the enabling environment for innovation in agriculture and food systems to unlock public funds to support researchers in developing their innovations. One way to implement this is through increased public funding for innovative agricultural research and development (R&D) efforts such as the Centre of Excellence in Science, Technology, and Innovation (CoE-STI) of the African Union Development Agency – New Partnership for Africa’s Development (AUDA-NEPAD) and CGIAR Accelerate for Impact Platform (A4IP). CoE-STI brings in a focus on innovation and R&D capacities toward the commercialisation of genome-edited agricultural products to improve livelihoods. CGIAR A4IP promotes the acceleration of the Sustainable Development Goals and food systems progress by valorising and connecting science-based solutions and innovators to deploy impactful solutions on the ground.